Problem Formulation and the Solution Strategies for Symmetric and Asymmetric Evacuation Networks (Prithvi Academic Journal, 2026)
Dynamic flow formulations are the basic mathematical tools for evacuation planning problems. They can be formulated to maximize flow, minimize time, or minimize cost, depending on the nature and context of the problem. However, for the evacuation system, the focus is on minimizing time while maximizing flow, so that the large number of evacuees can be evacuated in the shortest possible time. Their effectiveness in evacuation systems mainly depends on network structures and available resources. In this research work, we consider the formulation of the evacuation planning problem and solution strategies to minimize clearance time in evacuation networks with symmetric and asymmetric topologies were considered. For this, we used the uniform path length network, grid network, and embedded network topologies to get the minimum clearance time on such specific networks. Depending upon the nature of the problem, different heuristic approaches are used to get their solutions.